The Social Applications of Smart Phones and Their Impact on Yarmouk University Students’ Exposure to Traditional Media - Tahat, Zuhair; Mohammadin, Ahmad; Tahat, Khalaf (Jordan Journal of Social Sciences, 2018)
The study aims to identify the impact of social applications of Smart phones on the students’ exposure to traditional media. The student population is all the students of Yarmouk University (YU) who registered for the first semester 2016/2017 totaling (6961). The study sample consists of (364) students from Yarmouk University who were selected randomly. The descriptive analytical approach was used. The study reaches a number of results namely: the social applications impact of Smart phones on the students’ exposure to traditional media in terms of reasons and motives of use at level ( 0.05), the social applications impact of Smart phones on the students’ exposure to traditional media in terms of freedom of interaction and expression at level ( 0.05), there are obstacles that limit the use of Yarmouk University students of traditional media at level ( 0.05). The study recommends conducting an in-depth study to identify obstacles of the use of smart phones by university students.